2006
DOI: 10.1111/j.1742-7843.2006.pto_348.x
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Enhances Antitumour Activity and Decreases Genotoxic Effect of Cyclophosphamide

Abstract: Ginsenoside Rh 2 , a panoxadiol saponins, possesses various antitumour properties. Cyclophosphamide, an alkylating agent, has been shown to possess various genotoxic and carcinogenic effects, however, it is still used extensively as an antitumour agent and immunosuppressant in the clinic. Previous reports reveal that cyclophosphamide is involved in some secondary neoplasmas. In this study, the antitumour activity and genotoxic effect of oral intake of ginsenoside Rh 2 combined with intraperitoneal injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…On the other hand, a DDI sometimes might benefit the patients by producing an enhanced effect from increased systemic levels of the target drug. The synergistic effect of Rh2 on anticancer therapies has already been reported (Jia et al, 2004;Wang et al, 2006;Xie et al, 2006). In the present study, the pharmacokinetic basis for this synergism was elucidated.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, a DDI sometimes might benefit the patients by producing an enhanced effect from increased systemic levels of the target drug. The synergistic effect of Rh2 on anticancer therapies has already been reported (Jia et al, 2004;Wang et al, 2006;Xie et al, 2006). In the present study, the pharmacokinetic basis for this synergism was elucidated.…”
Section: Discussionmentioning
confidence: 88%
“…Ginsan, which itself is not mutagenic, decreases the frequency of micronucleated polychromatic erythrocytes induced by gamma radiation in bone marrow cells of C57BL/6 male mice (Ivanova et al, 2006). Similarly, the ginsenoside Rh 2 enhances the antitumor activity and decreases the genotoxicity of cyclophosphamide in mice (Wang et al, 2006). Ginseng has powerful antioxidant (Cho et al, 2008) and antimutagenic (Geetha et al, 2006;Ivanova et al, 2006) properties, although the mechanisms of these protective effects remain to be elucidated.…”
Section: Antigenotoxic Effects Of Panax Ginseng 949mentioning
confidence: 99%
“…Ginsenoside Rh2s is one of the most studied ginsenosides because it displays potent anticancer activity, especially in lung cancer cell lines (Cheng et al, 2005;Wang et al, 2006). A 9-week animal study also showed that Rh2s had a tendency to decrease lung tumor incidence in mice after its oral consumption (Yun, 2003).…”
Section: Introductionmentioning
confidence: 99%